2017
DOI: 10.1016/j.yfrne.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine disruption in animal models due to exposure to bisphenol A analogues

Abstract: Animal and human studies provide evidence that exposure to the endocrine disrupting chemical (EDC), bisphenol A (BPA), can lead to neurobehavioral disorders. Consequently, there is an impetus to identify safer alternatives to BPA. Three bisphenol compounds proposed as potential safer alternatives to BPA are bisphenol S (BPS), bisphenol F (BPF), and bisphenol AF (BPAF). However, it is not clear whether these other compounds are safer in terms of inducing less endocrine disrupting effects in animals and humans w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 133 publications
2
44
1
Order By: Relevance
“…In such products, BPA has been replaced by other substances, including bisphenol S (BPS), bisphenol AF and bisphenol F (BPF), and goods produced without BPA are labeled as “BPA‐free” products, which are considered safe for humans and animals. Nevertheless, recent studies have shown that substitutes for BPA may (like BPA) leach from plastic‐ware into water and food, absorbed into body fluids and tissues and may also have a negative impact on living organisms by causing several pathological conditions . For example, it is known that BPS (the most widely used substitute for BPA) has hormonal potencies with the same magnitude as BPA .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such products, BPA has been replaced by other substances, including bisphenol S (BPS), bisphenol AF and bisphenol F (BPF), and goods produced without BPA are labeled as “BPA‐free” products, which are considered safe for humans and animals. Nevertheless, recent studies have shown that substitutes for BPA may (like BPA) leach from plastic‐ware into water and food, absorbed into body fluids and tissues and may also have a negative impact on living organisms by causing several pathological conditions . For example, it is known that BPS (the most widely used substitute for BPA) has hormonal potencies with the same magnitude as BPA .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent studies have shown that substitutes for BPA may (like BPA) leach from plastic-ware into water and food, absorbed into body fluids and tissues and may also have a negative impact on living organisms by causing several pathological conditions. 73,74 For example, it is known that BPS (the most widely used substitute for BPA) has hormonal potencies with the same magnitude as BPA. 75 It causes reproductive dysfunctions and affects the GI tract, where it significantly inhibits digestive enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…These restrictions led to the alternative use of BPA analogues, including bisphenol AF (BPAF), bisphenol F (BPF) and bisphenol S (BPS) 22 . Environmental monitoring has now identified high concentrations of these bisphenol A analogues in foodstuffs, indoor dust, sediments, sewer effluents, sludge, soils, river and sea waters in various countries 4,6,22,23 and measurable amounts can now be detected in human biological samples such as urinary samples, 24,25 maternal sera and umbilical cord sera 26 …”
Section: Introductionmentioning
confidence: 99%
“…In rodent and human foetal testis explants (ex vivo), BPS and BPF decrease basal testosterone secretion 34 . Importantly, an increased number of recent in vivo studies suggest that several BPA analogues act as endocrine disrupters in rodent and fish models 26 …”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of both in vitro and in vivo studies has suggested that the potency in hormonal effect of BPF is in the same order of magnitude as that of BPA (Rochester and Bolden 2015). More recent studies have confirmed the similarities in the reported biological effects between BPF and BPA (Goldinger et al 2015;Kim et al 2017;Lee et al 2017;Mesnage et al 2017;Rosenfeld 2017). Zoller Disclaimer The opinions expressed here are those of the authors and do not reflect the views of EFSA or FSVO.…”
Section: Introductionmentioning
confidence: 68%